A Psychologist-Led Educational Intervention Results in a Sustained Reduction in Neonatal Intensive Care Unit Infections - Van Rostenberghe, Hans; Short, Jacki; Ramli, Noraida; Geok, Tan Beng; Subramaniam, Sivasangari; Che Yaakob, Che Anuar; Othman, Azizah; Ibrahim, Nor Rosidah; Ho, Jacqueline; Mohamed, Zeehaida; Hasan, Habsah (Frontiers in Pediatrics, 2014)
Even though in the corporate world psychological science has been widely used, the formal use of evidence- based psychology in important areas of clinical medicine has been scanty at best. It was the aim of this study to determine the efficacy of a psychologist-led two-week nurse educator training on the infection rate in the NICU. Materials and methods: Six senior neonatal nurses underwent in 2007 a training course covering the retrieval of evidence and knowledge of psychological principles that would allow them to share the evidence in such a way that evidence is effectively brought into practice. The course was led by a psychologist. The nurses created and delivered their own teaching modules, all focused on infection control. The rates of bacteraemia, 2 years prior to intervention were analyzed and compared with the rate following the intervention for three years. Results: The immediate output of the course included three teaching modules (hand washing, sterile procedures, general measures to control infection). These modules were subsequently administered to the NICU nurses in structured and regular continuous nursing education (CNE) sessions. The psychological techniques taught in the course were applied. Bacteraemia in the NICU significantly decreased in the year of the course and the subsequent years when compared to previous years. Conclusion: This study suggests that a psychologist-led course, followed by a structured CNE can lead to a sustainable reduction in infection rates in a NICU.